2010
DOI: 10.1029/2009jd013022
|View full text |Cite
|
Sign up to set email alerts
|

Coastal observations of weather features in Senegal during the African Monsoon Multidisciplinary Analysis Special Observing Period 3

Abstract: During 15 August through 30 September 2006 (Special Observing Period 3, SOP3), key weather measurements are obtained from ground and aircraft platforms during the African Monsoon Multidisciplinary Analysis campaign. Key measurements are aimed at investigating African easterly waves (AEWs) and mesoscale convective systems in a coastal environment as they transition to the eastern Atlantic Ocean. Ground and aircraft instruments include polarimetric radar, a coarse and a high‐density rain gauge network, surface c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Previous studies indicated distinct differences in the dynamic and thermodynamic characteristics of MCSs that propagate through West Africa and, in some cases, over the Atlantic Ocean [ DeLonge et al ., ; Jenkins et al ., ; Guy et al ., ]. Previous studies employed satellite and radar data to examine convection and rainfall in West Africa [ Fuentes et al ., ; Nicholls and Mohr , ; Guy and Rutledge , ].…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies indicated distinct differences in the dynamic and thermodynamic characteristics of MCSs that propagate through West Africa and, in some cases, over the Atlantic Ocean [ DeLonge et al ., ; Jenkins et al ., ; Guy et al ., ]. Previous studies employed satellite and radar data to examine convection and rainfall in West Africa [ Fuentes et al ., ; Nicholls and Mohr , ; Guy and Rutledge , ].…”
Section: Introductionmentioning
confidence: 98%
“…The SAL is characterized by dry (low relative humidity), stable air (an inversion above the marine boundary layer), a midlevel easterly jet and reduced visibilities from enhanced dust [ Carlson and Prospero , 1972; Karyampudi and Carlson , 1988; Dunion and Velden , 2004]. The SAL is evident from vertical profiles of temperature, dew point and relative humidity from coastal cities of Mauritania, Senegal [ Jenkins et al , 2010] and the Cape Verde Islands [ Zipser et al , 2009]. Recent lidar measurements have detected aerosols suspended in the SAL exiting West Africa is typically found between 2 and 6 km [ Léon et al , 2009].…”
Section: Introductionmentioning
confidence: 99%
“…The present analysis deals with rainfall data of the Dakar raingauge network, located in the region of Dakar (Senegal) in the vicinity of the coast (Jenkins et al, 2010). The rain-gauge network ( Figure 1) We first consider precipitating events.…”
Section: Rain-gauge Datamentioning
confidence: 99%